Highly efficient quenching of tris(2, 2′-bipyridyl)ruthenium(ii) electrochemiluminescence by ozone using formaldehyde, methylglyoxal, and glyoxalate as co-reactants and its application to ozone sensing. Issue 12 (21st June 2015) - Gao, Ying; Liu, Xiaoyun; Qi, Wenjing; Gao, Wenyue; Li, Yunhui; Xu, Guobao
<x xml:space="preserve">Abstract</x> Ozone can dramatically quench tris(2, 2′-bipyridyl)ruthenium(ii) ECL of formaldehyde, methylglyoxal, and glyoxalate, enabling highly sensitive ozone detection.